Examining the marketing-corporate social responsibility nexus - Hinson, R.; Kodua, p. (My University, 2012)
Purpose – The purpose of this paper is to examine how corporate social responsibility is incorporated into marketing strategy for a leading telecommunications firm (MTN) in Ghana. The paper examines the corporate social responsibility practices of this firm by focussing on various dimensions of stakeholder interests, norms and values. Design/methodology/approach – A conceptual framework was adopted from the extant literature and used as the basis for the single case study analysis. The authors interviewed senior management of the company and also analysed corporate social responsibility (CSR) information posted on the company's website. Findings – MTN has a strong commitment to social responsibility programmes. A separate independent unit, dubbed, “MTN Foundation”, has been established with its own Board of Directors and management team to manage CSR-related programmes. However, there seems to be lack of coordination of activities of other departments such as marketing and human resources which are of equal interest to major stakeholders. Again, in an effort to identify stakeholders' interests, there appears to be a lack of a proactive approach in examining the actual needs of prospective beneficiaries of CSR programmes of the company. Originality/value – The paper serves as a guide to managers in the planning and implementation of social responsibility programmes within the context of developing countries and also adds to the relatively parsimonious literature on CSR practices of firms operating in Africa.
Keywords: Corporate; Ghana; Marketing; MTN; Social responsibility